Leadership styles of female academicians in Malaysiaan public universities / Nik Nor Hasimah Nik Ismail and Nurul Syaqirah Zulqernain - Nik Ismail, Nik Nor Hasimah; Zulqernain, Nurul Syaqirah (Universiti Teknologi Mara Cawangan Kelantan, 2020)
This paper is a preliminary study on the leadership styles of female academicians in Malaysia’s public universities. Over the years, leadership styles have been studied extensively in various contexts, with different theoretical foundations. Leaders have been traditionally seen in many cultures as those who have benefited from their heritage, but current theorists and researchers view leadership as learned behaviours. The growing impact of women in the workforce has kept the leadership style of women on the research agenda. This study adopted the leadership style model by Bass and Avolio. Respondents were given a set of questionnaires from the Multifactor Leadership Questionnaire (MLQ) to identify their leadership styles. The questionnaires contained 18 questions based on Bass and Avolio’s Multifactor Questionnaire. Preliminarily, 200 academicians were chosen from 20 public universities in Malaysia. Apart from determining the leadership styles of these academicians, the study also tried to search for any distinct relationship (if any) between gender and leadership styles. It was found that the leadership styles of these academicians are more towards transactional leadership or task-oriented. Transactional Leadership is based on bureaucratic authority and legitimacy within the organisation. Transactional leaders emphasise work standards, assignments, and task-oriented goals. They also tend to focus on task completion and employee compliance and rely quite heavily on organisational rewards and punishments to influence employee performance. In contrast, Transformational Leadership is a process that motivates follower s by appealing to higher ideals and moral values. Transformational leaders must be able to define and articulate a vision for their organisations, and the followers must accept the credibility of the leader. The findings showed that a higher percentage of female academicians are transactional leaders. This means that they are more task-oriented rather than people-oriented